A novel multi trait genotype ideotype distance index (MGIDI) for genotype selection in plant breeding: Application, prospects, and limitations - Pinki Debnath; Kakon Chakma; M. Shafi Ullah Bhuiyan; Reshma Thapa; Ronghui Pan; Delara Akhter (Crop Design, 2024)
The Multitrait Genotype Ideotype Distance Index (MGIDI) is a strong and adaptable technique for choosing superior genotypes of diverse crops based on numerous attributes. It is a multivariate selection indicator that incorporates different characteristic information into a single value and ranks genotypes based on their distance from an ideal genotype. Breeders can use variable selection criteria including weighting traits and assessing genetic strengths and weaknesses. It organizes attributes into components and chooses optimal genotypes based on many traits using principal component analysis. This review covered the available information regarding the background, applications, prospects, and limitations of MGIDI for crop improvement and breeding in this research. We discussed the significant discoveries and consequences of several studies that used MGIDI to enhance the productivity, excellence, and flexibility of numerous crops, such as bush yam, barley, cassava, cucumber, guar, lentil, maize, rice, bean, soybean, wheat, etc. Additionally, we talked about some of the potential applications of MGIDI for breeding and crop improvement, such as tolerance to salinity, stability analysis, tolerance to waterlogging, mechanism of drought response, performance in agronomy and tuber quality, nutritional value and productivity, adaptability, increased yield, early maturity, and stress resistance etc. Following the upward trend, MGIDI can be considered as a valuable index technique for selection of crop genotypes that can address food security, climate change, and nutritional quality problems worldwide. We expect that this study will spark more research and use of MGIDI in different crops characteristics, contributing to the improvement of plant breeding science.